Stock price reactions to climate science information from the Intergovernmental Panel on Climate Change: A mitigation function of corporate and sector emissions responsibility? - Constanze Teutrine; Mario Schuster; Sophie Constance Bornhöft; Rainer Lueg; Yassin Denis Bouzzine (Business Strategy and the Environment, 2024)
This research investigates the influence of climate science information released by the Intergovernmental Panel on Climate Change (IPCC) on the European stock market, with a particular emphasis on differentiating the stock price reactions based on sector climate sensitivity and corporate emissions responsibility. Performing an event study on Stoxx Europe 600 constituents, we analyse stock price reactions to the sixth IPCC assessment report published between 2018 and 2023. Results show that climate-sensitive sectors respond more intensely to climate news. We find greater volatility in stock prices for climate-sensitive sectors than in corporate emissions-graded portfolios. Cumulative average abnormal returns range from 26.442% for the alternative energy sector to -6.416% for the construction sector. For the corporate emissions responsibility portfolios, we generally observe negative stock price reactions disregarding firms' level of emissions responsibility. Firms with higher emissions responsibility outperform peers only during the synthesis report release. Our study enriches the literature on stock price reactions to climate science news, which is limited to the analysis of the first five IPCC reports and to sector analyses.
Keywords: 330; climate risk; climate sensitivity; environmental responsibility; event study; IPCC; stock market reaction